FRATRICIDE IN OTTOMAN LAW - (:unkn) unknown (TURK TARIH KURUMU, 2018)
This paper considers fratricide in the Ottoman Empire from the Islamic/Ottoman Law viewpoint. The established Turkish political tradition, which is based on the fact that the ruling power is a common patrimony of the members of the dynasty, gave rise to disastrous results in the early period of the Ottoman Empire. Since a strict succession system was not imposed during that early period of the Ottoman State, it would be the destiny of a shahzadah (prince) which would determine his fate in becoming the next sultan. This resulted in infighting amongst the shahzadahs. Revolting against the sultan or even planning to revolt are crimes according to Islamic/Ottoman law The execution of those members of the dynasty who had not taken part in a revolt was legislated by the Code of Sultan Mehmed the Conqueror, which was based on the sovereign right of the sultan accorded by Islamic Law (Orfi Hukuk). Relying on the principle of maslaha (common benefit) in Islamic law, some of the Ottoman scholars permitted fratricide as well. According to this principle, when facing two potential outcomes, the lesser of two evils is preferred. Some of the modern researchers consider this justification invalid. According to them, the execution of shahzadahs who have not taken part in a revolt is politically correct, but contrary to Islamic law The main contribution of this paper is to deal with the fratricide from the point of view of Islamic law by utilizing traditional legal texts and to addess to underlying Islamic legal principles behind fratricide application and what legal evidence the 'ulema, (Ottoman scholars) based their judgment on.
Keywords: succession; primogenitur; seniorat; ulash; Code of Sultan Mehmed the Conqueror; Kanunname-i Al-i Osman; Ottoman Law; Islamic Law; maslaha; common benefit; nizam-i 'alem; shahzadah; orfi hukuk; revolt; rebellion; ta'zeer; siyaseten qatl; baghy; khuruj ala al-sultan; sai bi al-fasad; siyasah